2018
DOI: 10.1155/2018/1695782
|View full text |Cite
|
Sign up to set email alerts
|

Positive Association between EDN1 rs5370 (Lys198Asn) Polymorphism and Large Artery Stroke in a Ukrainian Population

Abstract: There are a lot of convincing evidences about the involvement of endothelin pathway proteins in the pathogenesis of atherosclerosis and its fatal complications. In this study, the analysis of a possible association between EDN1 rs5370 and EDNRA rs5335 gene polymorphisms and the risk of large artery stroke (LAS) in a Ukrainian population was conducted. 200 LAS patients and 200 unrelated controls were enrolled in a case-control study. The polymerase chain reaction-restriction fragment length polymorphism method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 35 publications
(43 reference statements)
0
12
0
2
Order By: Relevance
“…Such SNP may not have influence on disease susceptibility however they can be an important maker if they coinherit with other highly disease-associated gene or with other highly functional SNP of same gene. Dubovyk et al (2018) and Zhang and Sui (2014) provided inconsistent results due to low statistical power. This may be due to a number of issues, including sample size, heterogeneous pathophysiology, and silent SVD.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Such SNP may not have influence on disease susceptibility however they can be an important maker if they coinherit with other highly disease-associated gene or with other highly functional SNP of same gene. Dubovyk et al (2018) and Zhang and Sui (2014) provided inconsistent results due to low statistical power. This may be due to a number of issues, including sample size, heterogeneous pathophysiology, and silent SVD.…”
Section: Discussionmentioning
confidence: 98%
“…Some studies have found that Lys198Asn is associated with ischemic stroke (Dubovyk, Oleshko, Harbuzova, & Ataman, 2018;Li Wei et al, 2009;Yamaguchi et al, 2006;Zhang & Sui, 2014). Some studies have found that Lys198Asn is associated with ischemic stroke (Dubovyk, Oleshko, Harbuzova, & Ataman, 2018;Li Wei et al, 2009;Yamaguchi et al, 2006;Zhang & Sui, 2014).…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 3 more Smart Citations